Security in Multi-Agent Systems - Hedin, Yaqin; Moradian, Esmiralda (Procedia computer science, 2015)
Multi-agent systems become more and more popular due to successful implementations in different fields. However, there is a number of threats that can compromise security of the agent and jeopardize systems security. Therefore, security issues should be taken into consideration during development of multi-agent systems. However, different existing methodologies that provide guidelines and models for development of multi-agent systems omit security. Therefore, there is a great need in offering security solutions which are integrated with system functionalities. This research presents a model for securing multi-agent systems, which is developed, based on the concepts and models regarding agent's role and communications. Moreover, possible attacks on multi-agent systems are presented and threats are categorized. Furthermore, general security requirements at the agent and the system levels are defined and considered in the proposed model.